Analytical hierarchy process on the implementation of multi lane free flow toll road transaction system in Indonesia - Saputra, Yanuar Ardiansyah; Latief, Yusuf (Edelweiss Applied Science and Technology, 2025)
The Indonesian government, through the Indonesia Toll Road Authority and the Ministry of Public Works and Housing, has established a policy for implementing an electronic toll transaction system for Multi-Lane Free Flow Toll Roads in Indonesia as an effort to improve the speed of toll transaction services. However, since it was first launched in 2016, until the beginning of 2024, this policy has not been implemented due to various problems. Therefore, this research will evaluate the key factors affecting the implementation of the electronic toll transaction system for Multi-Lane Free Flow Toll Roads in Indonesia and develop the best alternative strategy for its implementation. This research will use a combination of qualitative and quantitative research methods with the application of the Analytical Hierarchy Process (AHP). The analysis found that there are seven main factors: public acceptance, legal framework, investment cost, technology, toll road performance, data, and stakeholders. The three factors that are considered the most influential based on AHP analysis are the legal framework at 25.7%, toll road performance at 18.18%, and public acceptance at 14.28%. At the indicator level, the top two rankings are the toll transaction time indicator at 12.38% and privacy and data protection at 8.34%. The results of the analysis recommend the best alternative strategy, which is the selection of the best electronic toll transaction system technology, with a value of 22.23%, outperforming four other alternative strategies.